RANCANG BANGUN MODEL PRODUCTION PRODUCTIVITY IMPROVEMENT DENGAN MENGGUNAKAN LEAN TPM DAN SISTEM DINAMIS - Intan Emeralda; Dorina Hetharia; Iveline Anne Marie (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
Increasing productivity and quality is one of the key to make company stay competitive. LeanTPM approach is one of the way to increase productivity. Problem that usually occur at PT. XYZ is thedown time from each line of process production that causing actual production did not reach the target.It is dominantly cause by material shortage, process defect, and machine breakdown. This purpose ofstudy is to develop a production productivity improvement model with Lean TPM approach by usingdynamic system. This study is started by measuring the Loss time value, OEE (Overall EquipmentEffectiveness) value, and making VSM (Value Stream Mapping) to see the flow of material and waste.This is done to measure the actual condition. With this measurement, we can track which one cause thehighest % loss. After that, using the FTA (Fault Tree Analysis) to find the root cause of downtime andwaste produced. It needed to construct the existing dynamic model because the problem are complexsand dynamic. In that model, analytical system is done to indentified and imitated the characteristic ofthose complex systems and also to make the alternative troubleshooting repair solution.